2021
DOI: 10.1080/0015198x.2021.1947024
|View full text |Cite
|
Sign up to set email alerts
|

Environmental, Social, and Governance Issues and the Financial Analysts Journal

Abstract: Over the last 75 years, the Financial Analysts Journal has commonly led other finance journals in featuring articles on environmental, social, and governance (ESG) issues. These articles have been written by academics, practitioners, and the journal's editors and always include a perspective of how these issues affect finance practice. In particular, the Financial Analysts Journal has been in the forefront with articles on the social responsibility of business and its investors; the performance of firms, inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 55 publications
0
8
0
1
Order By: Relevance
“…For discussions on the history of investing based on values, see, for example,Renneboog, ter Horst, and Zhang (2008) andStarks (2021).4 Consistent with the terminology confusion discussed above, ESG investing could also be shown as encompassing both SRI and impact investing. I have displayed them as distinct in order to highlight the differences.5 Impact investing usually involves expectation of receiving both financial and social returns, where the social returns are based on both intentionality and additionality.…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…For discussions on the history of investing based on values, see, for example,Renneboog, ter Horst, and Zhang (2008) andStarks (2021).4 Consistent with the terminology confusion discussed above, ESG investing could also be shown as encompassing both SRI and impact investing. I have displayed them as distinct in order to highlight the differences.5 Impact investing usually involves expectation of receiving both financial and social returns, where the social returns are based on both intentionality and additionality.…”
mentioning
confidence: 84%
“…Additional studies on ESG ratings and stock returns include Brandon Gibson,Krueger, and Schmidt (2021) andBerg et al (2021).15 Whether a business should pay particular attention to environmental and social issues (or whether they should practice social responsibility) has been a subject of debate among finance academics and practitioners for many years. For examples of earlier contributions, seeStarks (2021).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Investors who invest in the companies through bonds have more potential than equity investors to adopt policies for carbon emissions through covenant in bond indenture (Focardi and Fabozzi, 2020). A structured review study (Starks, 2021) identified a lack of standards and comparability across firms, a lack of reliable data and a need for quantifiable ESG data as critical issues concerning ESG information. In a distinct study (Azar et al ., 2021) studied the role of three big institutional investors (i.e.…”
Section: Mapping the Trends In Esg Research In The Last Five Years (2...mentioning
confidence: 99%
“…ESG menjelaskan serangkaian faktor yang digunakan untuk mengukur dampak non-keuangan dari investasi dan perusahaan tertentu. Pada saat yang sama, ESG juga menyediakan berbagai peluang bisnis dan investasi (Starks, 2021). Meskipun informasi ESG mungkin tidak memiliki standarisasi, para ahli berpendapat bahwa informasi tersebut dapat membantu beradaptasi dengan perubahan lingkungan dan bahkan menjadi bagian dari strategi kompetitif perusahaan (Giannopoulos et al, 2022).…”
Section: Environmental Social and Governance (Esg)unclassified